KONTRIBUSI MUSIK KLASIK SEBAGAI IRINGAN TARIAN BALLET DI ROYAL BALLET CENTRE MEDAN - Johana Teresia Purba (Grenek: Jurnal Seni Musik, 2018)
This study aims to find out the background of the use of classical music as Balletdance accompaniment, whatever classical music title used as Ballet danceaccompanist, and how the contribution of classical music as Ballet danceaccompaniment.This research is based on a theoretical explanation of the meaningof contribution, classical music, music accompaniment and Ballet dance. Thisresearch was conducted in September 2017 until November 2017. This researchuses Qualitative Descriptive method, which become population and sample in thisresearch is Ballet students at Intermedite level at Royal Ballet Center Medan. Thisresearch takes place on Jl. General Ahmad Yani No 104 A Medan. The data werecollected by observation, interview, visual / drawing / documentation, literaturestudy and triangeles.The results of this study indicate that the contribution ofclassical music as Ballet dance accompaniment that is as one motion of relaxation,motion confirmation, atmosphere builder, trigger memory and as an illustration.Classical music contributes greatly to Ballet dance accompaniment. Whenperforming the initial stage or heating the music used is Le Cygne. Movement isdone at this stage is the plie movement, then in the second stage or core of the musicused is Swan Lake, then the move is done Swan Lake dance that resembles themovement of swans, movements performed in accordance with the classical musicused